Ai for marketing and product innovation : powerful new tools for predicting trends, connecting with customers, and closing sales - Pradeep, A. K. (Gildan Audio, 2019)
Get on board the next massive marketing revolutionAI for Marketing and Product Innovation offers creatives and marketing professionals a non-tech guide to artificial intelligence (AI) and machine learning (ML)-twin technologies that stand poised to revolutionize the way we sell. The future is here, and we are in the thick of it; AI and ML are already in our lives every day, whether we know it or not. The technology continues to evolve and grow, but the capabilities that make these tools world-changing for marketers are already here-whether we use them or not. This book helps you lean into the curve and take advantage of AI's unparalleled and rapidly expanding power. More than a simple primer on the technology, this book goes beyond the "what" to show you the "how": How do we use AI and ML in ways that speak to the human spirit' How to we translate cold technological innovation into creative tools that forge deep human connections' Written by a team of experts at the intersection of neuroscience, technology, and marketing, this book shows you the ins and outs of these groundbreaking technological tools.